EXPRESSION OF CONCERN: Status of high-impact scientific publication in nursing in Latin America - Espinoza-Véliz, Miriam Zulema; Espiritu-Martinez, Antony Paul; Espinoza-Egoavil, Melvi Janett; Usuriaga-Palacios, Maribel Nerida; Bazualdo-Fiorini, Enzo Renatto; Hilario Rivas, Jorge Luis; Bernedo-Moreira, David Hugo (EAI Endorsed Transactions on Pervasive Health and Technology, 2024)
Concerns have been raised over the peer review and editorial processes involving this article. The full notice can be found here: https://doi.org/10.4108/eetpht.11.12763